Fiqh Hisab Arah Kiblat: Kajian Pemikiran Dr. Ing Khafid dalam Software Mawāqit - Budiwati, Anisah (Unisia, 2018)
This study analyzes the software determining the direction of Qibla by Dr. Ing. Khafid, geodesy experts in BIG (Goespasial Information Agency) in Mawāqit version 2001.06. The analysis was conducted using qualitative methods. These results indicate that the system of reckoning Qibla direction of Dr. Ing. Khafid is in Mawāqit program version 2001.06. using calculations spherical trigonometry. In addition, see the pattern fiqh qibla direction, he sought to translate the arguments Shar’ie existing in the language of science in line with the opinion of Imam Syafi‟i, although there are differences.